Treatment of thyroid associated ophthalmopathy with periocular injections of triamcinolone. Issue 11 (15th October 2004) - Ebner, R; Devoto, M H; Weil, D; Bordaberry, M; Mir, C; Martinez, H; Bonelli, L; Niepomniszcze, H
Abstract : Aim: To evaluate the efficacy of periocular triamcinolone acetonide for the treatment of thyroid associated ophthalmopathy (TAO), and the presence of ocular or systemic adverse effects. Methods: A multicentre prospective pilot study was performed on patients diagnosed with Graves' ophthalmopathy less than 6 months before entry to the study. Patients were admitted to the study and were randomised into two groups: treatment and control. The treatment group received four doses of 20 mg of triamcinolone acetate 40 mg/ml in a peribulbar injection to the inferolateral orbital quadrant. Both groups were evaluated by measuring the area of binocular vision without diplopia on a Goldmann perimeter and the size of the extraocular muscles on computed tomography (CT) scans. Ophthalmological and systemic examinations were done to rule out ocular and systemic adverse effects. Follow up was 6 months for both groups. Results: 50 patients were eligible for the study. 41 patients completed the study. There was an increase in the area of binocular vision without diplopia in the treatment group (Σ initial: mean 231.1 (SD 99.9) and final absolute change, mean 107.1 (SD 129.0)) compared to the control group (Σ initial: mean 350.7 (SD 86.5) and final absolute change, mean −4.5 (SD 67.6)). The sizes of the extraocular muscles were reduced in the treatment group (mean (inferior rectus initial values): 1.3 (0.7), final percentage change: −13.2 (25.7), medial rectus initial values: 1.2 (0.6), final percentage change: −8.2 (20.7), superior rectus-levator palpebrae initial values: 1.2 (0.6), final percentage change: −9.5 (29.1), lateral rectus initial values: 1.0 (0.4), final percentage change: −11.5 (20.6)) compared to the control group (inferior rectus initial values: 0.9 (0.3), final percentage change: −4.0 (21.5), medial rectus initial values: 0.9 (0.3), final percentage change: 0.6 (22.4), superior rectus-levator palpebrae initial values: 0.9 (0.3), final percentage change: 12.5 (37.5), lateral rectus initial values: 0.9 (0.4), final percentage change: −0.5 (31.6)). Both measurements (degree of diplopia and muscle thickness) were statistically significant between groups (initial − final). No systemic or ocular adverse effects were found. Conclusions: Triamcinolone administered as a periocular injection is effective in reducing diplopia and the sizes of extraocular muscles in TAO ophthalmopathy of recent onset. This form of treatment is not associated with systemic or ocular side effects.